Unexpected positive cultures in presumed aseptic revision spine surgery using sonication. (May 2019) - Pumberger, M.; Bürger, J.; Strube, P.; Akgün, D.; Putzier, M.
Abstract : Aims: During revision procedures for aseptic reasons, there remains a suspicion that failure may have been the result of an undetected subclinical infection. However, there is little evidence available in the literature about unexpected positive results in presumed aseptic revision spine surgery. The aims of our study were to estimate the prevalence of unexpected positive culture using sonication and to evaluate clinical characteristics of these patients. Patients and Methods: All patients who underwent a revision surgery after instrumented spinal surgery at our institution between July 2014 and August 2016 with spinal implants submitted for sonication were retrospectively analyzed. Only revisions presumed as aseptic are included in the study. During the study period, 204 spinal revisions were performed for diagnoses other than infection. In 38 cases, sonication cultures were not obtained, leaving a study cohort of 166 cases. The mean age of the cohort was 61.5 years (sd 20.4) and there were 104 female patients Results: Sonication cultures were positive in 75 cases (45.2%). Hardware failure was the most common indication for revision surgery and revealed a positive sonication culture in 26/75 cases (35%) followed by adjacent segment disease (ASD) in 23/75 cases (30%). Cutibacterium acnes and Staphylococcus epidermidis were the most commonly isolated microorganisms, observed in 45% and 31% of cases, respectively. C. acnes was isolated in 65.2% of cases when the indication for revision surgery was ASD. Conclusion: Infection must always be considered as a possibility in the setting of spinal revision surgery, especially in the case of hardware failure, regardless of the lack of clinical signs. Sonication should be routinely used to isolate microorganisms adherent to implants. Cite this article: Bone Joint J 2019;101-B:621–624.